2020
DOI: 10.2147/cmar.s238172
|View full text |Cite
|
Sign up to set email alerts
|

<p>circRNA MYLK Accelerates Cervical Cancer via Up-Regulation of RHEB and Activation of mTOR Signaling</p>

Abstract: Background: Growing evidence directly suggested that circular RNAs (circRNAs) are crucial contributors in the course of cervical cancer (CC) onset and progression. Nevertheless, a large number of circRNAs have not been fully addressed in their function and underlying mechanisms during CC etiology. Purpose: Our study focused on the function of circRNA MYLK (myosin light chain kinase), one novel tumor-related circRNA, in CC cell behaviors. Methods: Firstly, we evaluated the expression profile of circMYLK in CC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Studies have shown that miR-1301-3p plays a dual role in tumor progression and can be used as a prognostic biomarker and therapeutic target for some malignant tumors [ 21–24 ]. In addition, miR-1301-3p was sponged by Circ_0004370, CircRNA MYLK and participated in cancer progression [ 25 , 26 ]. Here, our results showed that miR-1301-3p mimic could partially reverse the effect of hsa_circ_0008583 overexpression on HCC cell progression, which indicated that hsa_circ_0008583 played a carcinogenic role in HCC by sponging miR-1301-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miR-1301-3p plays a dual role in tumor progression and can be used as a prognostic biomarker and therapeutic target for some malignant tumors [ 21–24 ]. In addition, miR-1301-3p was sponged by Circ_0004370, CircRNA MYLK and participated in cancer progression [ 25 , 26 ]. Here, our results showed that miR-1301-3p mimic could partially reverse the effect of hsa_circ_0008583 overexpression on HCC cell progression, which indicated that hsa_circ_0008583 played a carcinogenic role in HCC by sponging miR-1301-3p.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circ_0000069 enhances the growth, migration, and invasion of CC cells via miR-873-5p/TUSC3 axis [ 19 ]. circ_MYLK facilitates CC progression by up-modulating RHEB and activating the mTOR signaling pathway [ 20 ]. Circ_AKT1 accelerates CC progression by up-modulating AKT1 through miR-942-5p [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circ-MYB proto-oncogene like 2 is reported to facilitate the proliferation and invasion of cc cells (37). Moreover, chen et al (38) suggested that circrna myosin light chain kinase could accelerate cell proliferation with si-hsa_circ_0101119 and sh-TCEAL6, HeLa cell proliferation was determined using an EdU assay (magnification, x200). (C) After co-transfection with si-hsa_circ_0101119 and sh-TCEAL6, the colony numbers of HeLa cells were detected with a colony formation assay (magnification, x100).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circ-MYB proto-oncogene like 2 is reported to facilitate the proliferation and invasion of CC cells ( 37 ). Moreover, Chen et al ( 38 ) suggested that circRNA myosin light chain kinase could accelerate cell proliferation and repress apoptosis via the upregulation of Ras homolog, mTORC1 binding and the activation of the mTOR pathway in CC. Wang et al ( 39 ) also revealed that the overexpression of hsa_circ_0001038 could promote cell proliferation and invasion by regulating cyclin-M3 and metastasis-associated in colon cancer 1 expression in CC.…”
Section: Discussionmentioning
confidence: 99%